1999
DOI: 10.2337/diabetes.48.5.1145
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor induces expression of VEGF receptor KDR through a protein kinase C and p44/p42 mitogen-activated protein kinase-dependent pathway.

Abstract: Vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) are angiogenic molecules whose combined mitogenic activity is potently synergistic. However, the molecular mechanism underlying this synergy is incompletely understood. We examined whether VEGF and bFGF affect expression of each other or alter expression of the VEGF receptor KDR in retinal capillary endothelial cells. In addition, we investigated the intracellular signaling mechanisms involved in this response. VEGF-induced [3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 52 publications
3
61
0
4
Order By: Relevance
“…[37][38][39] This imbalance of vascular growth and differentiation signals was reported to lead to disruption of vascular integrity and to produce a phenotype reminiscent of that observed in the current study. 40,41 Our experiments comparing the effects of wild-type FGF-1 (without and with additional FGF-BP) and a form of FGF-1 engineered to be secreted supports the proposed mechanism of action of FGF-BP, that is, to enhance the activity of locally stored FGFs.…”
Section: Discussionsupporting
confidence: 46%
“…[37][38][39] This imbalance of vascular growth and differentiation signals was reported to lead to disruption of vascular integrity and to produce a phenotype reminiscent of that observed in the current study. 40,41 Our experiments comparing the effects of wild-type FGF-1 (without and with additional FGF-BP) and a form of FGF-1 engineered to be secreted supports the proposed mechanism of action of FGF-BP, that is, to enhance the activity of locally stored FGFs.…”
Section: Discussionsupporting
confidence: 46%
“…sponse of endothelial cells to VEGF by upregulating the VEGFR-2 (flk-1/KDR) (Hata et al, 1999). Thus FGF-2-induced endothelial sensitivity to VEGF that is expressed within the developing stroma or secreted by tumor cells that are transformed could potentiate early tumor-associated stromal angiogenesis.…”
Section: Claffey Et Almentioning
confidence: 99%
“…It would be of value to test this possibility by investigating whether FGF2-induced CEC proliferation involves the autocrine action of VEGF. The induction of the expression of the VEGF receptor KDR by FGF2 in retinal capillary endothelial cells, con®rms that VEGF signalling is regulated by FGF2 (Hata et al, 1999). VEGF may play a central role in choroidal angiogenesis by mediating functions other than proliferation.…”
Section: Fgf2 But Not Vegf Is a Potent Mitogen For Cecmentioning
confidence: 99%
“…In order to rule out this hypothesis, it would be of value to analyse the e ects of FGF2 and VEGF on primary CEC cultures. It was recently reported that VEGF induced proliferation of macrovascular endothelial cells including human umbilical vein endothelial cells (HUVEC) and bovine aortic endothelial cells in vitro (Pedram et al, 1998;Yu and Sato 1999;, whereas it was une ective on bovine retinal capillary endothelial (BREC) cells in culture condition of low serum concentration (Hata et al, 1999). Overexpression of a negative dominant for FGFR1 in the choroid of mice induces a decrease in the normal neovascularization of the choroid during development (A Bikfalvi, personal communication).…”
Section: Fgf2 But Not Vegf Is a Potent Mitogen For Cecmentioning
confidence: 99%